2020
DOI: 10.3390/ijerph17176290
|View full text |Cite
|
Sign up to set email alerts
|

Process Mining-Supported Emergency Room Process Performance Indicators

Abstract: Emergency room processes are often exposed to the risk of unexpected factors, and process management based on performance measurements is required due to its connectivity to the quality of care. Regarding this, there have been several attempts to propose a method to analyze the emergency room processes. This paper proposes a framework for process performance indicators utilized in emergency rooms. Based on the devil’s quadrangle, i.e., time, cost, quality, and flexibility, the paper suggests multiple process p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Also, Battineni et al , by using a PM case study and extracting data from a hospital information system, evaluated the performance of the system with time indicators available in any PM tool (Battineni et al , 2019). Recently, some articles analyzed the performance of emergency rooms' processes by PM (Antunes et al , 2019; Cho et al , 2020), and also, it has been shown how insightful PM can be in health and safety performance (Pika et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, Battineni et al , by using a PM case study and extracting data from a hospital information system, evaluated the performance of the system with time indicators available in any PM tool (Battineni et al , 2019). Recently, some articles analyzed the performance of emergency rooms' processes by PM (Antunes et al , 2019; Cho et al , 2020), and also, it has been shown how insightful PM can be in health and safety performance (Pika et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In these situations aggregation of the events into a single node better represents the action associated with this process. Detecting the set of nodes which need aggregation is based on a graph-theoretical concept of graph clustering 14 . Node aggregation is based on the time-lag between the events as well as the event labeling -to avoid unique but simultaneous events from being aggregated.…”
Section: Node Aggregationmentioning
confidence: 99%
“…al. proposed several common ED process measures which could be evaluated through this method, yet recommendations for which data to use and what events to measure remains unclear [14].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies examine collaboration patterns between different healthcare professionals (e.g., nurse, physician, medical assistant) using network analysis [ 44 ] as well as the interplay of departments using a role interaction model [ 45 ]. Since collaboration and process efficiency are imperative in ER, optimization of an ER layout [ 46 ] or a development of process performance indicators for ER [ 47 ] is also performed.…”
Section: Introductionmentioning
confidence: 99%